Ethnobotanical Study of Identification of Traditional Medicinal Plants in the Community of Kedungombo Village, Baturetno District, Wonogiri Regency - Fety Fatimah; Tri Wiharti; Nur Rokhimah Hanik (Jurnal Biologi Tropis, 2023)
This study aims to identify the ethnobotany of traditional medicinal plants in the people of Kedungombo Village, Baturetno District, Wonogiri Regency. The research was carried out in Kedungmbo Village which consisted of 8 hamlets namely Gembol Hamlet, Kedungombo, Kedunggaleng, Setren, Nayu, Beji, Koripan and Klegen. The method used was a descriptive exploratory survey and semi-structured interview techniques with 40 respondents. There are 21 types of medicinal plants used as traditional medicine by the Kedungombo Village Community and are divided into 14 families. In the Zingiberaceae family there are turmeric, galangal, ginger kencur, curcuma. the Myrtaceae family has guava and salam, the Euphorbiaceae family has tentir and katuk, the Annonaceae family has srikaya and ylang flowers, the Rutaceae family has lemon, the Piperaceae family has betel, the Fabaceae family dadap serep, the Poaceae family has betel, the Rubiaceae family has noni, the Araceae family there is dringo, the Moringaceae family has moringa, the Lamiaceae family has basil, the Asphodelaceae family has aloe vera, the Pandanacea family has pandan. The most used part of the plant is the leaf with 43% utilization percentage and 29% rhizome. The people of Kedungombo Village use medicinal plants by boiling, consuming them directly, eating them, rubbing them on, and mashing them until smooth and then attaching them to the injured or painful parts.